A decade evolution of virtual and remote laboratories - Andini, Nurul Fajriah; Dewi, Popy Maulida; Marida, Tyas Agung Cahyaning; Wibawa, Aji Prasetya; Nafalski, Andrew (Association for Scientific Computing Electrical and Engineering, 2023)
The conventional-experimental laboratory has problems of times, expenses, risks, distances, and spaces. A potential solution to such problems is a virtual and remote laboratory. It uses web or mobile applications and internet networks for virtual learning. This paper discusses the recent development of virtual and remote laboratories in the last decade. An in-depth literature review is performed to discover any facts about VR laboratory development. The results of this review may lead to the future development of virtual and remote laboratories.